Analysis Of Maqasid Syariah On The Legal Development Of The Halal Industry As A Form Of Consumer Protection - Hasni, Hasniati; Lubi, Rahmat Husein (Al-Muamalat Jurnal Hukum dan Ekonomi Syariah, 2023)
Development The halal industry is very fast in Indonesia so it is a concern society. There is halal industry is expected capable collaborate, adapt, proficient technology and capability increase connection to all layers society. With development of industry from various sector, then as a Muslim demands must be in accordance with Islamic law, namely halal and thoiyib. Therefore it is necessary exists supervision law from government. Based on matter the purpose of doing this research is to analyze law halal industry as a form protection for consumers using analysis maqashid sharia. The research used is qualitative descriptive with approach normative juridical. Data collection techniques using primary data and secondary data obtained from laws, books, journals, scientific articles and literature reviews, as well as collected using library research Then analyzed by method descriptive qualitative. The results of this study known that analysis Maqasid sharia against the law halal industry as a form of protection for consumers is in accordance with Islamic teachings and can ensure the security public in consuming products and services.